The long-term impact of a change in Effort-Reward imbalance on mental health-results from the prospective MAN-GO study - Barrech, Amira; Riedel, Natalie; Li, Jian; Herr, Raphael M.; Moertl, Kathrin; Angerer, Peter; Guendel, Harald (European Journal of Public Health, 2017)
Background: Little is yet known on the long-term effects of stress management interventions (SMIs) in the workplace. The aim this study was to prospectively examine the effect of an improvement of psychosocial working conditions measured by the Effort-Reward (E-R) Imbalance model within 2 years following an SMI, and mental health 7 years later. Methods: The study sample consisted of 97 male industrial workers from southern Germany. Data were collected pre- and post-intervention in 2006 (T1) and 2008 (T2), respectively, as well as in 2015 (T3). Change scores were computed by subtracting T1 from T3 values. The associations between E-R ratio at T1, T2 and the change score, respectively, with depression and anxiety 7 years later were estimated by means of linear regression analysis. Analyses were adjusted for baseline levels of the exposure and outcome variables, socio-demographic-, health- and work-related covariates. Results: Within-person comparisons revealed a significant reduction (i.e. improvement) in E-R ratio post-intervention (-0.103, SD 0.24, P = 0.000). This improvement in the E-R ratio was significantly associated with lower anxiety (β = 0.358, P = 0.001) and depression (β = 0.246, P = 0.031) scores in the fully adjusted models. The association between change scores and mental health were slightly stronger than associations with absolute values at T1 and T2. Conclusions: An improvement in E-R ratio following an SMI, was significantly associated with lower anxiety and depression 7 years later. These results strongly support the importance of improving psychosocial working conditions in order to protect the mental health of employees in the long-run.
CRIS-Team Scopus Importer:2022-11-28